Urban Planners with Renewable Energy Skills - Nuorkivi, Arto Emerik; Ahonen, Anna-Maija (TeMA - Journal of Land Use, Mobility and Environment, 2013)
There is no much tradition to combine urban and energy planning together to fight Climate Change even though energy production with fossil fuels is the main cause to the Change. Pilot training of urban planners in five EU countries such Finland, Germany, Hungary, Spain and the United Kingdom to understand the basics of renewable energy sources (RES) and energy efficiency (EE) has been carried out during 2011-2012 under co-financing of Intelligent Energy Europe. Organizing such pilot training was challenging for many reasons, but the outcome can be consdered highly statisfactory, based on the recorded feedback of trainees and other stakeholders. The project encourages other planning schools in Europe to learn from the experience and to use the published training materials available in ten languages in their curricula.